The Fruits of Faith in the Last Day - Nodal Study - - Khalaf , Shehab; Hamd , khayal (Islamic Sciences Journal, 2023)
ABSTRACT The fruits of faith are brought together by the goodness of the world , the hereafter and their good deeds. Faith is the most important thing that the Prophet Muhammad taught his companions, who brought it to the ummah, and all goodness resulted from it. Faith in the Last Day guide people to the beneficial deeds and help those who believe in Allah to be patient remain calm when they face disasters and difficulties in their life. Because Allah promised them the good part in the hereafter.